2018
DOI: 10.1186/s12886-018-0761-y
|View full text |Cite
|
Sign up to set email alerts
|

A cost-effectiveness study of ICT training among the visually impaired in the Netherlands

Abstract: BackgroundDue to the ageing population, the number of visually impaired people in the Netherlands will increase. To ensure the future availability of services in rehabilitative eye care, we aim to assess the cost-effectiveness of information and communication technology (ICT) training among visually impaired adults from a societal perspective, using primary data from two large rehabilitative eye care providers in the Netherlands.MethodsParticipants were asked to fill in a questionnaire, which used six differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 12 publications
(2 reference statements)
3
16
0
Order By: Relevance
“…Nine of the 22 studies reported results from full economic evaluations (assessing both costs and outcomes): six cost-effectiveness analyses [ 49 , 50 , 57 62 ] (two of these were feasibility studies), and three cost-consequence analyses [ 15 , 63 65 ]. Thirteen studies reported partial economic evaluations, of which five were pilot or feasibility studies.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Nine of the 22 studies reported results from full economic evaluations (assessing both costs and outcomes): six cost-effectiveness analyses [ 49 , 50 , 57 62 ] (two of these were feasibility studies), and three cost-consequence analyses [ 15 , 63 65 ]. Thirteen studies reported partial economic evaluations, of which five were pilot or feasibility studies.…”
Section: Resultsmentioning
confidence: 99%
“…Some of the 22 studies evaluated interventions falling clearly within the health domain (such as telehealth [57, 58]; techniques/hardware used in hip fracture surgery [66, 67]; screening for those at risk of lung cancer [68]; comprehensive assessment and personalised clinical management strategies to reduce incontinence and nocturia for older adults following hip fracture [53]; comprehensive assessment for frail older people receiving acute hospital care [56]; and a pharmaceutical product [55]. However, most of the studies that were identified evaluated interventions relating to care in a community setting/self-care and/or integrated services for those with chronic and long-term conditions, where broader elements of quality of life (such as maintaining independence) would be more obviously and/or directly affected; the interventions here included: integrated health and social care [49, 52]; control over budgets for older people receiving community care in Australia [48]; a dementia self-management group [63]; a goal setting programme to promote healthy ageing and prevent dementia for those with low (or zero) needs [60]; information and communication technologies (ICT) training for those with a visual impairment [50]; interventions targeting post-acute needs [46, 54, 64, 65, 69]; and a programme of community activities aimed to help those with low (or zero) level needs to improve and maintain well-being [70]. Milne et al studied the impact of GPS devices for those with a cognitive impairment [15] and Boots et al assessed the impact of a blended care self-management program for family caregivers of people with early cognitive impairment [51].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The presentation of results in the included economic evaluations demonstrate that there is a lack of consensus regarding the most appropriate way to use capability instruments in economic evaluations. Some authors present cost and outcome data separately and conduct a cost-consequence analysis [42][43][44][45], whilst others reported the results following the idea behind the incremental cost-effectiveness ratio (ICER) [31,46]. This lack of consensus about the use of capability instruments in decision making relates to the different approaches taken by different research groups to valuation, which means that in practice these measures are not comparable along the lines of a QALY.…”
Section: Applied Economic Evaluations and Potential Methods To Incorpmentioning
confidence: 99%